2021
DOI: 10.1021/acs.iecr.0c05580
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Homogeneity under Selective and Localized Microwave Heating in Structured Flow Reactors

Abstract: Selective heating of different phases of multiphase systems via microwaves can result in energy savings and suppression of side reactions. However, materials properties and operating conditions that maximize temperature gradients are poorly understood. Here we utilize computational fluid dynamics (CFD) computations and temperature measurements in structured flow reactors (monoliths) in a monomodal microwave cavity to assess the temperature difference between the walls and the fluid and develop a simple lumped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Electrified heating is more versatile than conventional heating. Electricity can be converted to heat via Joule heating, , microwave heating, and induction heating. , Apart from being greener when renewable electricity is used, electrified reactors exhibit short startup times, low-temperature gradients, and cooler gases that can suppress gas-phase side reactions and lower energy use. Recently, examples of electrification have been demonstrated.…”
mentioning
confidence: 99%
“…Electrified heating is more versatile than conventional heating. Electricity can be converted to heat via Joule heating, , microwave heating, and induction heating. , Apart from being greener when renewable electricity is used, electrified reactors exhibit short startup times, low-temperature gradients, and cooler gases that can suppress gas-phase side reactions and lower energy use. Recently, examples of electrification have been demonstrated.…”
mentioning
confidence: 99%
“…The results obtained can be discussed as follows: it is expected that under IH regulation, the temperature variation on the catalyst surface, consecutive to the increase in the gaseous reactant velocity which induces higher gas-solid heat exchange, was rapidly regulated via fast heating adjustment, which thus, allows the maintenance of the reaction temperature and the desulfurization performance. A recent study by Malhotra et al 47 on the heat behavior inside the catalytic reactor operated under selective and localized microwave heating has reported a similar fact about the influence of the reactant flow rate on the surface temperature of the catalyst. According to the simulation results, the reactant flow rate has almost no influence on the catalyst temperature under microwave heating as only the catalyst, with high response heating rate, was heated, while the reactant gas-phase entering the catalytic bed remains cold.…”
Section: Nitrogen-doped Mesoporous Carbon Coated On Sicmentioning
confidence: 67%
“…Structured catalysts should reduce arcing due to their monolithic structure and uniform heating. [233][234][235] Furthermore, unlike liquid-liquid systems, the measurement of solid temperatures is not straightforward. Finally, while elevated solid temperatures could certainly enhance rates, it has not been demonstrated that this is the sole reason for enhanced performance.…”
Section: Electrication Using Microwaves (Mws)mentioning
confidence: 99%